CARDIAC PATHOLOGIES: HEMODYNAMIC ASSESSMENT AND COMPLICATIONS - Bohn, Taciara; de Oliveira, Vítor Antunes; Fiorin, Pauline Brendler Goettems; Frizzo, Matias Nunes (Seven Editora, 2026)
Cardiovascular diseases are the leading cause of mortality worldwide and remain a major challenge for public health in Brazil, especially in light of population aging and the high prevalence of cardiometabolic risk factors. In this context, hemodynamics, or interventional cardiology, plays a central role in the diagnosis and minimally invasive treatment of coronary syndromes and other cardiovascular pathologies. This chapter discusses the physiology of myocardial blood flow, the epidemiology of heart diseases, and the main clinical entities associated with coronary obstruction, with emphasis on atherosclerosis, angina, acute myocardial infarction, and heart failure. It also addresses the main procedures performed in hemodynamic services, such as cardiac catheterization, coronary angiography, coronary angioplasty, and stent implantation, emphasizing their indications and technical foundations. In addition, the text examines complications related to these procedures, especially vascular complications and events associated with arterial access routes, such as hematoma, spasm, pseudoaneurysm, radial artery occlusion, and contrast-induced nephropathy. Finally, the chapter reinforces the need for careful patient assessment, continuous monitoring, and early identification of clinical and laboratory predictive factors in order to reduce complications, improve patient safety, and enhance outcomes in hemodynamics.